2014
DOI: 10.5901/mjss.2014.v5n20p1439
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Perceptions of the Determinants of Reputation in South African Public Schools

Abstract: This research focuses on perceptions of reputation in black township

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…The corporate reputation of HEIs Universities are therefore likely to design programs based on five dimensions of corporate social responsibility that include community, economy, environment, employees and student's needs. These dimensions were tested in a university and confirmed that social responsibility plays a significant role in building the organizational reputation of a university and public schools (Kwatubana, 2014;Abedtalas et al, 2019).…”
Section: Factors Influencing Reputationmentioning
confidence: 84%
See 4 more Smart Citations
“…The corporate reputation of HEIs Universities are therefore likely to design programs based on five dimensions of corporate social responsibility that include community, economy, environment, employees and student's needs. These dimensions were tested in a university and confirmed that social responsibility plays a significant role in building the organizational reputation of a university and public schools (Kwatubana, 2014;Abedtalas et al, 2019).…”
Section: Factors Influencing Reputationmentioning
confidence: 84%
“…This systematic review focussed on HEIs, including high schools. Three studies (Skallerud, 2011;Badri and Mohaidat, 2014;Kwatubana, 2014) investigated the corporate reputation of high schools and primary schools.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations